Does nature’s contributions to people value realization policy in China improve public awareness and preferences for marine biodiversity conservation? A temporal stability analysis - Liu, Dandan; Li, Jingmei; Shan, Jingzhu; Shi, Fangyuan (Frontiers in Marine Science, 2024)
Management policies are crucial for safeguarding sustained and stable marine biodiversity amidst ongoing pressures such as land use change, pollution, resource overexploitation, invasive alien species and climate change. China established a nature's contributions to people value realization policy (NCPVR) in 2021, aiming to encourage stakeholders to prioritize environmentally beneficial production and consumption choices, thereby stimulating intrinsic public motivation for ecological conservation. Biodiversity conservation is an integral component of the NCPVR policy. A choice experiment method was employed to investigate the changes in public preferences for marine biodiversity conservation in Jiaozhou Bay before and after the enactment of the NCPVR policy (in 2017 and 2023, respectively), aiming to evaluate the effectiveness of the policy on marine biodiversity conservation. The results indicate that two years after the implementation of the NCPVR, the public's overall breadth and depth of awareness regarding marine biodiversity increased. Additionally, public preferences for marine biodiversity conservation increased, expanding from two categories in 2017 (shallow-water swimming organisms and marine plants) to five categories in 2023 (with the addition of seabirds, plankton, and intertidal and benthic organisms). The willingness to pay (WTP) for seabirds, plankton, and intertidal and benthic organisms, as well as shallow-water swimming organisms, increased from 32.21~85.77 CNY/person•year to 98.21~140.49 CNY/person•year. China's NCPVR policy effectively conveyed important information about biodiversity conservation in the short term, enhancing public awareness and preferences for marine biodiversity conservation. The study also revealed that economic incentive policies for NCPVR remain at the conceptual propaganda level and lack operational incentives for biodiversity conservation. It is recommended that the government deepen the design of value realization pathways and market trading arrangements to stimulate the intrinsic motivation of the public for marine biodiversity conservation and ensure the long-term effectiveness of policies.